2020
DOI: 10.1002/brb3.1867
|View full text |Cite
|
Sign up to set email alerts
|

The changed functional status of the brain was involved in patients with poststroke aphasia: Coordinate‐based (activation likelihood estimation) meta‐analysis

Abstract: Language impairment is one of the clinical manifestations of stroke. The estimated prevalence of poststroke aphasia (PSA) ranges from 21% to 38% (Berthier, 2005). Patients with PSA suffer not only isolated social emotions (Kauhanen et al., 2000), depression (Bullier et al., 2020), and low quality of life (Wang et al., 2018) but also speech impairment. Speech impairment may be improved by using cortical stimulation or pharmacotherapy. However, half of PSA patients recover much or all

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Our observation that left superior parietal activation was also enhanced in patients with damage to other left and right hemisphere regions may help to explain why the left superior parietal cortex (along with several other regions) was found, in a meta-analysis, to be hyperactivated during resting state fMRI in patients with aphasia compared with healthy adults ( Du et al. 2020 ).…”
Section: Discussionmentioning
confidence: 84%
“…Our observation that left superior parietal activation was also enhanced in patients with damage to other left and right hemisphere regions may help to explain why the left superior parietal cortex (along with several other regions) was found, in a meta-analysis, to be hyperactivated during resting state fMRI in patients with aphasia compared with healthy adults ( Du et al. 2020 ).…”
Section: Discussionmentioning
confidence: 84%
“…Using meta-analyses, Zhang et al in 2021 reported the relationship between the damage of dual-pathway tracts and language function impairment, addressing the neural mechanism of the Dual-Pathway White Matter [ 43 ]. Du et al's study compared regional activation between poststroke aphasia patients and healthy volunteers, implying the significance of dominant and nondominant language networks [ 24 ]. Though these studies provided valuable findings, they did not focus on the specific treatment of poststroke aphasia.…”
Section: Discussionmentioning
confidence: 99%